NK Cell Precursors in Human Bone Marrow in Health and Inflammation - Bozzano, Federica; Perrone, Carola; Moretta, Lorenzo; De Maria, Andrea (Frontiers in Immunology, 2019)
Similar to other blood cells, NK cells are generated from hematopoietic stem cells (HSC) residing in the bone marrow (BM). The BM harbors multipotent Lin-CD34+CD45RA+CD10+CD38+ common lymphoid progenitors (CLP) generating in vitro T, B, NK and Dendritic Cells that are devoid of erythroid, myeloid, and megakaryocytic potential. In addition, CD7 coexpression on CD34+CD45RA+ HSCs also enriches for NK cell precursors. Indeed, unipotent Lin-CD34+CD38+CD123-CD45RA+CD7+CD10+CD127- NK cell progenitors devoid of other lymphoid lineage potential have been described. These precursors, either unipotent or CLPs, have been characterized in healthy adult donors also in other secondary lymphoid tissues and thymus, and have been shown to be the main source for the staged NK cell development occurring in secondary lymphoid tissues under healthy, steady state conditions. More recently, compelling evidences in animal models have shown that inflammation plays a fundamental role in the regulation of HSC maturation and release in the BM niches through several mechanisms including modulation of the CXCL12-CXCR4 expression. Indeed during systemic inflammation, a different CLPs, namely Lin-CD34+DNAM-1brightCXCR4+ overwhelmingly exit the BM and prevail in PB over conventional CD34+DNAM-1-CXCR4- cells. The developmental fate of these “inflammatory” precursors is towards NK and T cells with a mature phenotype and highly functional program. Our understanding of NK cell precursor development may benefit from including in our modelling a distinct “inflammatory” deployment from the BM of specialized Lin-CD34+DNAM-1brightCXCR4+ resources, mirroring the steady state maintenance of the NK cell pool by Lin-CD34+DNAM-1-CXCR4- BM precursors.